Genetic analysis of nonalcoholic fatty liver disease within a Caribbean–Hispanic population. Issue 6 (11th August 2015) - Edelman, Deborah; Kalia, Harmit; Delio, Maria; Alani, Mustafa; Krishnamurthy, Karthik; Abd, Mortadha; Auton, Adam; Wang, Tao; Wolkoff, Allan W.; Morrow, Bernice E.
Abstract: We explored potential genetic risk factors implicated in nonalcoholic fatty liver disease (NAFLD) within a Caribbean–Hispanic population in New York City. A total of 316 individuals including 40 subjects with biopsy‐proven NAFLD, 24 ethnically matched non‐NAFLD controls, and a 252 ethnically mixed random sampling of Bronx County, New York were analyzed. Genotype analysis was performed to determine allelic frequencies of 74 known single‐nucleotide polymorphisms (SNPs) associated with NAFLD risk based on previous genome‐wide association study (GWAS) and candidate gene studies. Additionally, the entire coding region of PNPLA3, a gene showing the strongest association to NAFLD was subjected to Sanger sequencing. Results suggest that both rare and common DNA variations in PNPLA3 and SAMM50 may be correlated with NAFLD in this small population study, while common DNA variations in CHUK and ERLIN1, may have a protective interaction. Common SNPs in ENPP1 and ABCC2 have suggestive association with fatty liver, but with less compelling significance. In conclusion, Hispanic patients of Caribbean ancestry may have different interactions with NAFLD genetic modifiers; therefore, further investigation with a larger sample size, into this Caribbean–Hispanic population is warranted. Abstract : We performed the first genetic investigation of Nonalcoholic fatty liver disease (NAFLD) in Hispanic patients of majority Caribbean descent. Genotype analysis was performed to determine allelic frequencies of 74 known single‐nucleotide polymorphisms (SNPs) associated with NAFLD risk. Results suggest that variations in PNPLA3 and SAMM50 may be correlated with NAFLD, and SNPs in CHUK and ERLIN1 may have a protective interaction in this population.